Literasi Media Digital bagi Pemilih Pemula di Aisyiyah Boarding School Bandung: Digital Media Literacy for Beginner Voters at Aisyiyah Boarding School Bandung - Drajat, Mohamad Subur; Chaerowati, Dede Lilis; Umar, Tia Muthiah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Novice voters are sometimes considered swing voters in unanimous choice decisions. Meanwhile, according to several surveys, the millennial generation is projected to have the highest proportion of voters in the 2024 elections. The proliferation of false information, sometimes referred to as fake news or hoaxes, is a significant challenge in the present digital age. Furthermore, novice voters represent the largest demographic of digital media consumers. Therefore, it is essential to provide rookie voters with sufficient knowledge and abilities to effectively discern and counteract the dissemination of false information. The objective of this PKM is to enhance the digital media literacy knowledge and abilities of novice voters at 'Aisyiyah Boarding School Bandung in preparation for the 2024 Election. During this PKM activity, participants acquired knowledge of election literacy, election political communication, and election digital media for inexperienced voters. They also developed skills to articulate their opinions about leaders and election participation, as well as the ability to critically evaluate election information as informed voters. The techniques employed encompass training, interactive dialogues, and practical application of the ABCD (Assets Based Community Development) methodology. The outcomes of PKM activities indicate a rise in participants' knowledge, as seen by the changes in scores on the pretest and posttest assessments. The average level of knowledge has shifted from moderate to high. The participant's proficiency in articulating thoughts about leaders and engaging in election participation, as well as their aptitude for becoming astute voters and their capacity to verify election material in digital media, also improved.